Comparative Evaluation of Four Potent Neospora caninum Diagnostic Antigens Using Immunochromatographic Assay for Detection of Specific Antibody in Cattle - Ragab M. Fereig; Hanan H. Abdelbaky; Yoshifumi Nishikawa (Microorganisms, 2021)
Neospora caninum is an intracellular protozoan parasite responsible for numerous abortion outbreaks and neonatal abnormalities in cattle. Rapid and accurate diagnosis is critical for N. caninum control owing to the lack of vaccine or drug-based control strategies. Herein, we evaluated the performance of four frequently used antigens in the diagnosis of N. caninum infection using immunochromatographic tests (ICTs) as a rapid, affordable, and field applicable tool. These antigens included recombinant proteins of N. caninum surface antigen 1 (NcSAG1), dense granule proteins 7 (NcGRA7) and 6 (NcGRA6), in addition to native Neospora lysate antigen (NLA). Our study revealed the utility of all antigen-based ICTs for detection of specific antibodies to N. caninum. However, the NcSAG1-based ICT was the best for detection of all control N. caninum-infected mouse or cattle sera, while NcGRA7 and NcGRA6-based ICTs exhibited specific ability to detect samples from acute and sub-acute infection in mice and cattle, respectively. Analyses of the NcSAG1-based ICT against enzyme-linked immunosorbent assays (ELISAs) of the same antigen revealed its efficiency in detection of field cattle samples as observed in high sensitivity (84.2%), specificity (93.5%), agreement (90%), and kappa value (0.78). The current knowledge provides an efficient platform for N. caninum control through on-site diagnosis of infected cattle.